Becoming Romano-British: The landscape of the late prehistoric and Romano-British periods in the Vale of the White Horse. - Wintle, W; William Wintle (2013)
This thesis investigates the rural landscape of the Vale of the White Horse in the late Iron Age and the Roman period. Its three aims are to place the Roman temple, amphitheatre and cemetery at Marcham / Frilford within the context of the wider rural landscape, to document the nature of the Romano-British social and economic structure and its relationship to earlier Iron Age systems, and to compare the rural community of the Vale with other communities in the upper Thames Valley. The first aim is addressed by analysing the archaeological data for the neighbourhood of the religious complex at Marcham / Frilford, integrating recent geophysical survey and commercial archaeological evaluations. It is considered whether the site's function was restricted to an extensive religious complex, or whether it can be classed as a small town. Although there is no evidence for urbanism in terms of densely packed buildings, market activities are possible. It is suggested that the cemetery might be a 'managed cemetery'. The second and third aims are addressed by presenting and evaluating the archaeological evidence for the use of the landscape. The development of the Iron Age into the Romano-British landscape is seen through changes in settlement density, structure and form, buildings such as villas, ditched field systems, communication via roads and trackways, increasing population and agricultural intensification. Variations in settlement forms in the Vale of the White Horse are considered within the wider context of settlement in the upper Thames Valley. The Iron Age landscape of the Vale appears similar to that of the gravel terraces north of the river Thames. In the Roman period it differs from the gravel terraces to the north by becoming a region of villas and local centres, which suggests differences in landholding and in social and economic structures. In addition, the late Iron Age and Romano-British settlement in the Vale of the White Horse is compared with other regional studies.